Surgery for retrohepatic caval thrombus in patients with advanced renal cell carcinoma: a case series. Issue 1 (December 2015) - Polańska-Płachta, Małgorzata; Proczka, Robert; Dudek, Magdalena; Ostrowska, Małgorzata; Polański, Jerzy
Abstract Background Thrombotic involvement of the inferior vena cava (IVC) occurs in about 10 % of all patients with renal cell carcinoma (RCC). It is treated with radical resection of tumor and thrombus. We present the results of a recent case series of 20 patients with retrohepatic IVC thrombus. Methods Our cohort of 20 patients included 16 primary resections (radical nephrectomy and thrombectomy with and without vascular graft), three recurrences primarily operated on elsewhere (thrombectomy and vascular graft), and one recurrence due to a new liver metastasis. Results All surviving patients were discharged with a patent IVC. The overall mortality rate was 10 %, and the overall complication rate was 35 %. Both are in keeping with results presented worldwide. Conclusions Our series provides a corroborating extension to the existing dataset on RCC-related IVC thrombus removal. It confirms that the radical surgical approach can be performed safely and successfully with respect to venous patency.